Maternal Mortality Determinants in Refferal Hospital : Three Years Retrospective Study - Morel Sembiring (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2017)
Background: Maternal mortality rate is one indicator used to assess overall women health status. According to the WHO, 99% of maternal deaths are delivery related and dominantly occur in developing countries. Objective: To determine the causes of maternal deaths at H. Adam Malik General Hospital Medan based on the following factors: remote determinants, the intermediate determinants, and outcome determinants as a risk factor of maternal deaths. Methods: This retrospective analytical study reviewed medical records of women who underwent delivery at H. Adam Malik General Hospital, Medan from January 1st 2010 until December 31th 2012. Data were statiscally analysed using a descriptive and inferential approach. Univariate, bivariate, and multivariate logistic regression analysis were used. Results: This study obtained as much as 681 complete medical records for 3 years, with 37 maternal deaths. Pre-eclampsia / eclampsia is the most common cause of death by 20 cases (54.1%). Maternal education degree, referral systems, facilities for delivery, history of systemic diseases, pregnancy and postpartum related complications were significantly correlated to the outcome of labor with OR of 1.97; 10.11; 41.36; 5.818; 3.49; and 685.7, respectively and p<0.05. Based on the multiple logistic regression test, maternal history of systemic diseases, pregnancy and postpartum related complications were the three factors that most significantly correlated to maternal mortality with p <0.05. Conclusion: Delivery outcomes were significantly associated with the followingfacrors: formal education, referral status, facilities for delivery, history of systemic diseases, mode of delivery, pregnancy and postpartum related complications. Maternal history of systemic diseases, pregnancy and postpartum related complicationswere the three factors that most significantly correlated to maternal mortality.